Mobile Commerce Model Taking Advantage of a Near Field Communication (NFC) - Olufemi, Akinyede Raphael; Boluwade, Rotimi Abiodun; Busola, Famodimu Oluwasefunmi; Elijah, Balogun Temitayo (Review of Computer Engineering Research, 2020)
This paper presents an alternative method of shopping using NFC which aims to be easy, user-friendly, and more convenient. In this system, the supermarket or mall with an existing electronic shopping system will incorporate the NFC technology. The application would be used by the customer to scan the NFC tags attached to the products in the store. All the items to be purchased will be listed on the application, customers can make the necessary adjustment to the quantity they want to purchase and can proceed to make payment using their ATM card details before proceeding to checkout. In traditional shopping spaces, people need to carry baskets all over the shopping mall, get the products they need and add them to their baskets. All the products in your baskets will be billed at the exit counter. This process creates a long queue for checkouts and payments at the exit counter. The overall shopping process takes up a lot of time and more manpower is needed to manage the large crowds. The application is developed using JavaScript as the programming language and Extensible Markup Language which enables us to build an application with a rich user interface, with the Integrated Development Environment platform as Android Studio. The project was implemented on an NFC enabled Samsung NOTE 3 device, 4gb ram, 32gb internal phone storage, Android 7.0.